Taking aim at Mer and Axl receptor tyrosine kinases as novel therapeutic targets in solid tumors - Linger, Rachel M.A. (2010)
IMPORTANCE OF THE FIELD: Axl and/or Mer expression correlates with poor prognosis in several cancers. Until recently, the specific role of these receptor tyrosine kinases (RTKs) in the development and progression of cancer remained unexplained. Studies demonstrating that Axl and Mer contribute to mechanisms of cell survival, migration, invasion, metastasis, and chemosensitivity justify further investigation of Axl and Mer as novel therapeutic targets in cancer. AREAS COVERED IN THIS REVIEW: Axl and Mer signaling pathways in cancer cells are summarized and evidence validating these RTKs as therapeutic targets in glioblastoma multiforme, non-small cell lung cancer, and breast cancer is examined. A comprehensive discussion of Axl and/or Mer inhibitors in development is also provided. WHAT THE READER WILL GAIN: Potential toxicities associated with Axl or Mer inhibition are addressed. We hypothesize that the probable action of Mer and Axl inhibitors on cells within the tumor microenvironment will provide a unique therapeutic opportunity to target both tumor cells and the stromal components which facilitate disease progression. TAKE HOME MESSAGE: Axl and Mer mediate multiple oncogenic phenotypes and activation of these RTKs constitutes a mechanism of chemoresistance in a variety of solid tumors. Targeted inhibition of these RTKs may be effective as anti-tumor and/or anti-metastatic therapy, particularly if combined with standard cytotoxic therapies.